Water-absorbent resin particles and absorbent article

By developing water-absorbing resin particles, the problem of excessive counterflow and diffusion area of ​​absorbent items for care is solved, and better water-absorbing performance and use effect are achieved.

CN119585041APending Publication Date: 2025-03-07SUMITOMO SEIKA CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055165.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing absorbent items for care have problems with excessive counterflow and diffusion area, which affects the sense of use and effect.

Method used

A water-absorbent resin particle has a water absorption rate of 3 to 30 seconds and a water absorption amount of 10 mL/g or more under load. The water absorption rate and water absorption amount under load are adjusted by a mixture containing different water-absorbent resin particles A and B to suppress the counterflow rate and diffusion area.

Benefits of technology

By using the water-absorbing resin particles, the counterflow rate and diffusion area of ​​the absorbent article for care can be significantly suppressed, and the sense of use and effect can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585041A_ABST
    Figure CN119585041A_ABST
Patent Text Reader

Abstract

Disclosed are water-absorbent resin particles having a water absorption rate of 3-30 seconds and a water absorption amount of 10 mL / g or more under a load of 2.07 kPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-absorbent resin particle and an absorbent article. Background Art

[0002] Water-absorbent resin particles are used in sanitary materials such as diapers, sanitary products, and nursing sheets; agricultural and horticultural materials such as water-retaining materials and soil improvement materials; industrial materials such as waterproof materials for cables and anti-condensation materials; animal excrement disposal materials such as pet mats and dog or cat toilet preparations; and simple toilets, fragrances, meat dripping absorbent sheets, or moisturizing cosmetic preparations, etc. For example, Patent Document 1 discloses a nursing absorbent article, i.e., a water-absorbent composite sheet, having a substrate and substantially spherical water-absorbent resin particles intermittently fixed to the substrate.

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-323842 Summary of the invention

[0006] Technical issues to be solved by the invention

[0007] The present invention relates to a water-absorbent resin particle capable of suppressing backflow and diffusion area and an absorbent article including the water-absorbent resin particle that can be used as a nursing absorbent article.

[0008] Means for solving technical problems

[0009] The present invention includes the following contents.

[0010] [Item 1] A water-absorbent resin particle having a water absorption rate of 3 to 30 seconds and a water absorption amount under a load of 2.07 kPa (hereinafter sometimes referred to as "water absorption under load") of 10 mL / g or more.

[0011] [Item 2] The water-absorbent resin particles according to Item 1, wherein the water absorption rate is 6 to 10 seconds and the median particle size is 150 μm or more.

[0012] [Item 3] The water-absorbent resin particles according to Item 1 or 2, comprising water-absorbent resin particles A and water-absorbent resin particles B, wherein the water absorption rate of the water-absorbent resin particles A is 5 seconds or less, and the water absorption amount of the water-absorbent resin particles A under a load of 2.07 kPa is 8 to 35 mL / g, and the water absorption rate of the water-absorbent resin particles B is 15 seconds or more, and the water absorption amount of the water-absorbent resin particles B under a load of 2.07 kPa is 20 to 35 mL / g.

[0013] [Item 4] An absorbent article comprising the water-absorbent resin particles according to any one of Items 1 to 3.

[0014] Effects of the Invention

[0015] By using the water-absorbent resin particles according to the present invention, it is possible to provide an absorbent article used as a nursing care article with a suppressed backflow amount and diffusion area. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a partial cross-sectional view showing an example of an absorbent article.

[0017] Figure 2 It is a schematic diagram showing an apparatus for measuring the water absorption under load of water-absorbent resin particles. DETAILED DESCRIPTION

[0018] Hereinafter, the water-absorbent resin particles according to the present invention and the absorbent article using the water-absorbent resin particles will be described. However, the present invention is not limited to the following examples.

[0019] In this specification, "acrylic acid" and "methacrylic acid" are collectively referred to as "(meth)acrylic acid". "Acrylic acid ester" and "methacrylic acid ester" are similarly referred to as "(meth)acrylate". In addition, "(poly)" means both the case with the prefix "poly" and the case without the prefix "poly".

[0020] In the numerical range of staged recording in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range of recording in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0021] The materials exemplified in this specification can be used alone or in combination of two or more. In the case where there are multiple substances equivalent to each component in the composition, unless otherwise specified, the content of each component in the composition represents the total amount of the multiple substances present in the composition.

[0022] In this specification, "room temperature" means 25±2°C. Furthermore, the term "layer" includes not only structures formed on the entire surface but also structures formed on a portion of the surface when viewed from above. "Physiological saline" means a sodium chloride aqueous solution with a concentration of 0.9 mass %.

[0023] [Characteristics of water-absorbent resin particles]

[0024] (Water absorption speed)

[0025] The water absorption rate of the water-absorbent resin particles according to the present invention is 3 to 30 seconds, but may be 4 to 30 seconds, 6 to 30 seconds, 7 to 30 seconds, 3 to 22 seconds, 3 to 18 seconds, 3 to 17 seconds, 3 to 13 seconds, 3 to 10 seconds, 4 to 22 seconds, 4 to 18 seconds, 4 to 17 seconds, 4 to 13 seconds, 4 to 10 seconds, 6 to 22 seconds, 6 to 18 seconds, 6 to 17 seconds, 6 to 13 seconds, 6 to 10 seconds, 7 to 22 seconds, 7 to 18 seconds, 7 to 17 seconds, 7 to 13 seconds or 7 to 10 seconds.

[0026] The above water absorption rate is the water absorption rate of physiological saline, and the specific measurement method is described in the examples described below.

[0027] (water retention capacity)

[0028] The water-retention capacity of the water-absorbent resin particles of the present invention may be, for example, 25 to 60 g / g, 25 to 55 g / g, 25 to 50 g / g, 25 to 47 g / g, 30 to 60 g / g, 30 to 55 g / g, 30 to 50 g / g, 30 to 47 g / g, 35 to 60 g / g, 35 to 55 g / g, 35 to 50 g / g, 35 to 47 g / g, 39 to 60 g / g, 39 to 55 g / g, 39 to 50 g / g, 39 to 47 g / g, 40 to 60 g / g, 40 to 55 g / g, 40 to 50 g / g, 40 to 47 g / g, 44 to 60 g / g, 44 to 55 g / g, 44 to 50 g / g or 44 to 47 g / g.

[0029] The water retention capacity is the water retention capacity of physiological saline, and the specific measurement method is described in the examples described below.

[0030] (Water absorption under load)

[0031] The water-absorbent resin particles according to the present invention have a water absorption capacity under a load of 2.07 kPa of 10 mL / g or more, but may be 10 to 30 mL / g, 10 to 25 mL / g, 10 to 22 mL / g, 10 to 20 mL / g, 10 to 19 mL / g, 15 to 30 mL / g, 15 to 25 mL / g, 15 to 22 mL / g, 15 to 20 mL / g, 15 to 19 mL / g, 17 to 30 mL / g, 17 to 25 mL / g, 17 to 22 mL / g, 17 to 20 mL / g, 17 to 19 mL / g, 18 to 30 mL / g, 18 to 25 mL / g, 18 to 22 mL / g, 18 to 20 mL / g or 18 to 19 mL / g.

[0032] The water absorption under load is the water absorption under load of physiological saline, and the specific measurement method is described in the examples described below.

[0033] (Median particle size)

[0034] The median particle size of the water-absorbent resin particles according to the present invention may be, for example, 150 μm or more, 150 to 400 μm, 150 to 380 μm, 150 to 360 μm, 150 to 300 μm, 150 to 250 μm, 170 to 400 μm, 170 to 380 μm, 170 to 360 μm, 170 to 300 μm, 170 to 250 μm, 200 to 400 μm, 200 to 380 μm, 200 to 360 μm, 200 to 300 μm, or 200 to 250 μm.

[0035] The specific method for measuring the median diameter is described in the examples described below.

[0036] The water-absorbent resin particles according to the present invention may be a powder composed of a single type of particles, or may be a particle mixture containing a plurality of types of particles having different physical properties in at least one of water absorption rate and water absorption under load.

[0037] When the water-absorbent resin particles are a particle mixture containing a plurality of particles, the particle mixture may contain at least the following water-absorbent resin particles A and water-absorbent resin particles B. The water absorption rate of the water-absorbent resin particles A is 5 seconds or less, and the water absorption amount of the water-absorbent resin particles A under a load of 2.07 kPa is 8 to 35 mL / g. The water absorption rate of the water-absorbent resin particles B is 15 seconds or more, and the water absorption amount of the water-absorbent resin particles B under a load of 2.07 kPa is 20 to 35 mL / g. The water-absorbent resin particles containing the water-absorbent resin particles A and the water-absorbent resin particles B can be produced by a method including the following steps: a powder of the water-absorbent resin particles A and a powder of the water-absorbent resin particles B are mixed to form the water-absorbent resin particles as a powder mixture.

[0038] The water absorption rate of the water-absorbent resin particles A may be 1 to 5 seconds, 1 to 4 seconds, 1 to 3 seconds, 2 to 5 seconds, 2 to 4 seconds, or 2 to 3 seconds. The water absorption under load of the water-absorbent resin particles A may be 8 to 30 mL / g, 8 to 25 mL / g, 8 to 23 mL / g, 8 to 20 mL / g, 8 to 15 mL / g, 10 to 30 mL / g, 10 to 25 mL / g, 10 to 23 mL / g, 10 to 20 mL / g, or 10 to 15 mL / g.

[0039] The water-retention capacity of the water-absorbent resin particles A may be 10 to 45 g / g, 10 to 40 g / g, 15 to 45 g / g, 15 to 40 g / g, 20 to 45 g / g, 20 to 40 g / g, 25 to 45 g / g, 25 to 40 g / g, 30 to 45 g / g, 30 to 40 g / g, 35 to 45 g / g or 35 to 40 g / g. The median particle size of the water-absorbent resin particles A may be 100 to 450 μm, 100 to 400 μm, 100 to 380 μm, 100 to 360 μm, 150 to 450 μm, 150 to 400 μm, 150 to 380 μm, 150 to 360 μm, 200 to 450 μm, 200 to 400 μm, 200 to 380 μm, 200 to 360 μm, 250 to 450 μm, 250 to 400 μm, 250 to 380 μm, 250 to 360 μm, 300 to 450 μm, 300 to 400 μm, 300 to 380 μm or 300 to 360 μm.

[0040] The water absorption rate of the water-absorbent resin particles B may be 15 to 60 seconds, 15 to 55 seconds, 15 to 45 seconds, 15 to 35 seconds, 15 to 25 seconds, 20 to 60 seconds, 20 to 55 seconds, 20 to 45 seconds, 20 to 35 seconds, 20 to 25 seconds, 25 to 60 seconds, 25 to 55 seconds, 25 to 45 seconds, 25 to 35 seconds, 30 to 60 seconds, 30 to 55 seconds, 30 to 45 seconds or 30 to 35 seconds. The water absorption under load of the water-absorbent resin particles B may be 20 to 30 mL / g, 20 to 25 mL / g, 25 to 35 mL / g, 25 to 30 mL / g or 30 to 35 mL / g.

[0041] The water-retention capacity of the water-absorbent resin particles B may be 30 to 60 g / g, 30 to 55 g / g, 30 to 50 g / g, 30 to 45 g / g, 35 to 60 g / g, 35 to 55 g / g, 35 to 50 g / g, 35 to 45 g / g, 40 to 60 g / g, 40 to 55 g / g, 40 to 50 g / g or 40 to 45 g / g. The median particle size of the water-absorbent resin particles B may be 100 to 450 μm, 100 to 400 μm, 100 to 380 μm, 100 to 360 μm, 150 to 450 μm, 150 to 400 μm, 150 to 380 μm, 150 to 360 μm, 200 to 450 μm, 200 to 400 μm, 200 to 380 μm, 200 to 360 μm, 250 to 450 μm, 250 to 400 μm, 250 to 380 μm, 250 to 360 μm, 300 to 450 μm, 300 to 400 μm, 300 to 380 μm or 300 to 360 μm.

[0042] When the water-absorbent resin particles include a plurality of types of particles, the ratio of the water-absorbent resin particles A to the water-absorbent resin particles B on a mass basis (mass of the water-absorbent resin particles A:mass of the water-absorbent resin particles B) may be 1:19 to 19:1, 1:19 to 9:1, 1:19 to 3:1, 1:19 to 13:7, 1:19 to 3:2, 1:19 to 1:1, 1:14 to 19:1, 1:14 to 9:1, 1:14 to 3:1, 1:14 to 13:7, 1:14 to 3:2, 1:14 to 1:1, 1:12 to 19:1, 1:12 to 9:1, 1:12 to 3:1, 1:12 to 13:7, 1:12 to 3:2, 1:12 to 1:1, 2:13 to 19:1, 2:1 3~9:1、2:13~3:1、2:13~13:7、2:13~3:2、2:13~1:1、2:15~19:1、2:15~9:1、2:15~3:1、2:15~13:7、2:15~3:2、2:15~1:1、3:17~19:1、3:17~9:1、3:17~3:1、 3:17 to 13:7, 3:17 to 3:2, 3:17 to 1:1, 1:3 to 19:1, 1:3 to 9:1, 1:3 to 3:1, 1:3 to 13:7, 1:3 to 3:2, 1:3 to 1:12:3 to 19:1, 2:3 to 9:1, 2:3 to 3:1, 2:3 to 13:7, 2:3 to 3:2 or 2:3 to 1:1. By controlling the mass ratio of the water-absorbent resin particles A to the water-absorbent resin particles B, various properties of the water-absorbent resin particles such as the water absorption rate and the amount of water absorbed under load can be controlled within an arbitrary range.

[0043] By using the water-absorbent resin particles of the present invention in a nursing absorbent article, the backflow and diffusion area of ​​the absorbent article can be suppressed. As a result, a good feeling of use can be imparted to the absorbent article. The present inventors speculate the mechanism as follows.

[0044] Since nursing absorbent articles (especially waterproof sheets used on beds or quilts) are used for a long time in a horizontal position by the user, the backflow amount and diffusion area have a great influence on the feeling of use. Therefore, absorbent articles with less backflow amount and narrow diffusion area are preferred. However, in absorbent articles, the reduction of backflow amount and the reduction of diffusion area are likely to become a relationship of checks and balances.

[0045] The inventors of the present invention initially focused on the above-mentioned trade-off relationship and believed that if the water absorption rate of the water-absorbent resin particles is adjusted to an appropriate value, an absorbent article in which both the backflow amount and the diffusion area are suppressed can be formed. In other words, the inventors generally focused on the fact that when the water absorption rate of the water-absorbent resin particles is too slow, the diffusion area tends to expand, while when the water absorption rate is too fast, the liquid is difficult to diffuse, and the backflow amount tends to increase. The inventors believed that if the water absorption rate is adjusted to an appropriate value, an absorbent article in which both the backflow amount and the diffusion area are appropriately suppressed can be formed.

[0046] However, according to the verification of the present inventors, even if only the water absorption rate is adjusted, it is impossible to obtain an absorbent article in which both the backflow and the diffusion area are appropriately suppressed with good reproducibility. As a result of studying the cause, the present inventors found that the water absorption under load is very important. That is, the present inventors found that even if the water absorption rate is an appropriate value, if the water absorption under load is too small, gel clogging is likely to occur, the diffusion area is excessively suppressed and the backflow is likely to increase. The clogging phenomenon is a phenomenon in which the liquid permeability deteriorates due to the gaps between the particles being filled with swollen water-absorbent resin particles (swollen gel). That is, the present inventors found that the amount of water absorption under load is an important factor affecting the backflow and diffusion area of ​​the absorbent article. The present inventors further conducted in-depth research and found that the load condition of the water-absorbent resin particles, which is the most suitable for evaluating absorbent articles, is preferably 2.07kPa. Regarding this load condition, the conditions under which absorbent articles are usually used (conditions under which pressure is applied by bedding, etc. laid on the upper surface of the absorbent article) are assumed. Based on this knowledge, the present inventors have found that an absorbent article in which both the backflow amount and the diffusion area are suppressed can be formed by using water-absorbent resin particles having a specific water absorption rate and a specific water absorption amount under load.

[0047] Furthermore, the inventors have found that, during verification, it is easier to obtain an absorbent article in which both the backflow amount and the diffusion area are suppressed when the absorbent resin particles A and the absorbent resin particles B are included than when a single type of absorbent resin particles is used. The inventors have investigated the mechanism as follows. By including the absorbent resin particles A and the absorbent resin particles B, the absorbent resin particles A having a relatively fast water absorption speed suppress the diffusion area, while the absorbent resin particles B having a relatively slow water absorption speed and a specific amount of water absorption under a load prevent the diffusion area from being suppressed excessively, thereby reducing the backflow amount. As a result, it is easy to obtain an absorbent article in which both the backflow amount and the diffusion area are suppressed.

[0048] [Method for producing water-absorbent resin particles]

[0049] The water-absorbent resin particles involved in the present invention may be, for example, a resin obtained by polymerizing a water-soluble ethylenically unsaturated monomer. The water-absorbent resin particles may include polymer particles of a polymer containing a water-soluble ethylenically unsaturated monomer. Examples of polymers constituting the water-absorbent resin particles include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft copolymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and partially neutralized products of polyacrylic acid. The polymer may be a cross-linked polymer cross-linked by a cross-linking agent. The cross-linking agent may be, for example, one or more selected from an internal cross-linking agent, an intermediate cross-linking agent, and a surface cross-linking agent described later.

[0050] Examples of methods for polymerizing water-soluble ethylenically unsaturated monomers include aqueous solution polymerization and reversed phase suspension polymerization in which polymerization is carried out in a hydrocarbon dispersion medium in the presence of a surfactant. Hereinafter, as an example of a method for producing water-absorbent resin particles according to the present invention, a case where reversed phase suspension polymerization is used will be described.

[0051] The method for producing water-absorbent resin particles by reverse phase suspension polymerization includes a polymerization step. The polymerization step is a step of mixing an oily liquid containing a hydrocarbon dispersion medium with an aqueous liquid containing an aqueous solvent and a water-soluble ethylenically unsaturated monomer to obtain a suspension in which the aqueous liquid is dispersed in the oily liquid, and then polymerizing the water-soluble ethylenically unsaturated monomer. The polymerization reaction in the polymerization step is a W / O type reverse phase suspension polymerization method in which the oily liquid (O) containing a hydrocarbon dispersion medium is used as a continuous phase and the aqueous liquid (W) containing water is used as a droplet-shaped discontinuous phase dispersed in the continuous phase.

[0052] <Composition of suspension>

[0053] [Aqueous liquid]

[0054] The aqueous liquid is a liquid dispersed in the oily liquid in the reverse suspension polymerization method. The aqueous liquid contains an aqueous solvent and a water-soluble ethylenically unsaturated monomer, and may also contain any additives. The additives may include, for example, an internal crosslinking agent, a thickener, a hydrophilic polymer dispersant, a free radical polymerization initiator, a chain transfer agent, a foaming agent, a metal chelating agent, or a combination thereof, which may be described later.

[0055] (1) Aqueous solvent

[0056] The aqueous solvent may be water, a hydrophilic organic solvent, or a mixed solvent comprising water and a hydrophilic solvent. When a mixed solvent is used, 90% by mass or more of the mixed solvent may be water. Examples of hydrophilic organic solvents include lower alcohols such as methanol, ethanol, and isopropanol, and ketones such as acetone and methyl ethyl ketone. The hydrophilic organic solvent may be used alone or in combination of two or more.

[0057] (2) Water-soluble ethylenically unsaturated monomers

[0058] As examples of water-soluble ethylenically unsaturated monomers, ethylenically unsaturated monomers containing at least one functional group selected from the group consisting of carboxyl, sulfonic, amide and amino groups can be cited. As water-soluble ethylenically unsaturated monomers, for example, (meth)acrylic acid (hereinafter, "acrylic acid" and "methacrylic acid" are collectively marked as "(meth)acrylic acid") and its alkali salts, 2-(meth)acrylamide-2-methylpropane sulfonic acid and its alkali salts, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-hydroxymethyl(meth)acrylamide, polyethylene glycol mono(meth)acrylate, N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate and diethylaminopropyl(meth)acrylamide. In the case where the water-soluble ethylenically unsaturated monomer contains an amino group, the amino group can be quaternized. Functional groups such as carboxyl groups and amino groups possessed by the monomers can function as functional groups capable of crosslinking in the surface crosslinking step described later. The water-soluble ethylenically unsaturated monomers may be used alone or in combination of two or more.

[0059] In the case where the water-soluble ethylenically unsaturated monomer has an acid group such as (meth) acrylic acid and 2-(meth) acrylamide-2-methylpropane sulfonic acid, the acid group can be neutralized by an alkaline neutralizing agent such as an alkali metal salt to form an alkaline salt. As the alkaline neutralizing agent, aqueous solutions such as sodium hydroxide, potassium hydroxide and ammonia can be mentioned. The alkaline neutralizing agent can be used alone or in combination of two or more. The degree of neutralization of all acid groups by the alkaline neutralizing agent can be 10 to 100 mol%, 30 to 90 mol%, 50 to 80 mol% or 60 to 78 mol%.

[0060] The water-soluble ethylenically unsaturated monomer may include at least one compound selected from the group consisting of (meth)acrylic acid and its salts, acrylamide, (meth)acrylamide and N,N-dimethylacrylamide, or may include at least one compound selected from the group consisting of (meth)acrylic acid and its salts and acrylamide. In addition, (meth)acrylic acid and its salts may be used from the perspective of easily achieving the above-mentioned water absorption speed and water absorption under load.

[0061] The concentration of the water-soluble ethylenically unsaturated monomer in the aqueous liquid may be in the range of 20% by mass to the saturation concentration, and may be 25 to 50% by mass, 30 to 45% by mass, or 35 to 42% by mass.

[0062] In addition to these water-soluble ethylenically unsaturated monomers, other monomers can also be used. Other monomers can be mixed in an aqueous solution containing the above-mentioned water-soluble ethylenically unsaturated monomers for use. The amount of the water-soluble ethylenically unsaturated monomer used relative to the total amount of monomers can be 70 to 100 mol%. The ratio of (meth) acrylic acid and its salts relative to the total amount of monomers can be 70 to 100 mol%.

[0063] (3) Internal crosslinking agent

[0064] The aqueous liquid may contain an internal crosslinking agent. The internal crosslinking agent may be a compound having two or more reactive functional groups, and examples thereof include di- or tri-(meth)acrylates of polyols such as ethylene glycol, propylene glycol, trimethylolpropane, glycerol, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerol; unsaturated polyesters obtained by reacting the above polyols with unsaturated acids (maleic acid, fumaric acid, etc.); bis(meth)acrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri-(meth)acrylates obtained by reacting polyepoxides with (meth)acrylic acid; di(meth)acrylates obtained by reacting polyisocyanates (toluene diisocyanate, hexamethylene diisocyanate, etc.) with hydroxyethyl(meth)acrylate. Carbamoyl esters; compounds having two or more polymerizable unsaturated groups such as allyl starch, allyl cellulose, diallyl phthalate, N,N',N"-triallyl isocyanurate, and divinylbenzene; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and polyglycerol polyglycidyl ether; halogenated epoxy compounds such as epichlorohydrin, epibromohydrin, and α-methyl epichlorohydrin; isocyanate compounds (2,4-toluene diisocyanate, hexamethylene diisocyanate, etc.). The internal crosslinking agent may be used alone or in combination of two or more.

[0065] The internal crosslinking agent may be a polyglycidyl compound or a diglycidyl ether compound. The internal crosslinking agent may include at least one compound selected from the group consisting of (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether.

[0066] By using an internal crosslinking agent, the obtained polymer is appropriately crosslinked, thereby suppressing the water solubility and being easily adjusted within the above-mentioned range of water retention capacity. The amount of the internal crosslinking agent can be 0.01 to 0.50 mmol, 0.01 to 0.30 mmol, 0.01 to 0.20 mmol, 0.01 to 0.18 mmol, 0.01 to 0.15 mmol, 0.05 to 0.50 mmol, 0.05 to 0.30 mmol, 0.05 to 0.20 mmol, 0.05 to 0.18 mmol, 0.05 to 0.15 mmol per 1 mol of the water-soluble ethylenically unsaturated monomer.

[0067] (3) Thickener

[0068] The aqueous liquid may contain a thickener. Examples of the thickener include hydroxyalkyl celluloses such as hydroxyethyl cellulose (HEC) and hydroxypropyl cellulose (HPC); hydroxyalkyl alkyl celluloses such as hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl ethyl cellulose; carboxyalkyl celluloses such as carboxymethyl cellulose; and carboxyalkyl hydroxyalkyl celluloses such as carboxymethyl hydroxyethyl cellulose. The thickener may be at least one compound selected from hydroxyalkyl cellulose, hydroxyalkyl alkyl cellulose, and carboxyalkyl hydroxyalkyl cellulose, and may be hydroxyethyl cellulose and / or hydroxypropyl cellulose, or may be hydroxyethyl cellulose. One type of the thickener may be used alone, or two or more types may be used in combination.

[0069] The amount of the thickener may be 0.05 to 20 parts by mass, 0.2 to 10 parts by mass, or 0.4 to 5 parts by mass relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer. The thickener can control the dispersion state of the aqueous liquid in the suspension. Specifically, when the aqueous liquid does not contain a thickener or contains a thickener with low viscosity, the aqueous liquid is more easily dispersed than when the aqueous liquid contains a thickener with high viscosity, so it is easy to obtain water-absorbent resin particles with a small particle size, that is, a large specific surface area and a fast water absorption rate.

[0070] (4) Hydrophilic polymer dispersant

[0071] The aqueous liquid may include a hydrophilic polymer dispersant. As the hydrophilic polymer dispersant, for example, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), polypropylene glycol, polyethylene glycol-polypropylene glycol block copolymer, polyglycerol, polyoxyethylene glycerol, polyoxypropylene glycerol, polyoxyethylene-polyoxypropylene glycerol copolymer and polyoxyethylene sorbitan fatty acid ester may be mentioned. Among them, the hydrophilic polymer dispersant may be at least one compound selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polypropylene glycol and polyglycerol. The hydrophilic polymer dispersant may be used alone or in combination of two or more.

[0072] The amount of the hydrophilic polymer dispersant may be 0.001 to 10 parts by mass, 0.005 to 5 parts by mass, 0.01 to 3 parts by mass, or 0.01 to 1.5 parts by mass based on 100 parts by mass of the water-soluble ethylenically unsaturated monomer.

[0073] By using a hydrophilic polymer dispersant, water-absorbent resin particles whose surfaces are modified to be hydrophilic can be obtained. As a result, the water absorption rate of the water-absorbent resin particles can be increased.

[0074] (5) Free radical polymerization initiator

[0075] The aqueous liquid may contain a radical polymerization initiator. As the radical polymerization initiator, an azo compound or a peroxide can be used.

[0076] Examples of the azo compounds include 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, 2,2'-azobis{2-[N-(4-chlorophenyl)amidino]propane} dihydrochloride, 2,2'-azobis{2-[N-(4-hydroxyphenyl)amidino]propane} dihydrochloride, 2,2'-azobis[2-(N-benzylamidino)propane] dihydrochloride Hydrochloride, 2,2'-azobis[2-(N-allylamidinyl)propane] dihydrochloride, 2,2'-azobis(2-amidinylpropane) dihydrochloride, 2,2'-azobis{2-[N-(2-hydroxyethyl)amidinyl]propane} dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-( 2-Imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(4,5,6,7-tetrahydro-1H-1,3-diazepin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(5-hydroxy-3,4,5,6-tetrahydropyrimidin-2-yl)propane] dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2- imidazolin-2-yl]propane} dihydrochloride, 2,2'-azobis(2-methylpropionamide) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].

[0077] Examples of the peroxide include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; organic peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl isopropyl peroxide, tert-butyl peracetate, tert-butyl perisobutyrate, and tert-butyl perpivalate; and hydrogen peroxide.

[0078] The free radical polymerization initiator may be used alone or in combination of two or more. When two or more free radical polymerization initiators are used simultaneously, the above-mentioned azo compound and peroxide can be used simultaneously. The azo compound used simultaneously may be at least one selected from 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazoline-2-yl]propane} dihydrochloride and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate. The peroxide used simultaneously may be at least one selected from potassium persulfate, ammonium persulfate, sodium persulfate and hydrogen peroxide.

[0079] The amount of the free radical polymerization initiator is, for example, 0.005 to 1 mol relative to 100 mol of the water-soluble ethylenically unsaturated monomer. When an azo compound and a free radical polymerization initiator other than the azo compound (e.g., a peroxide) are used simultaneously, the ratio of the azo compound to the free radical polymerization initiator as a whole can be 10 to 100 mol%, 25 to 90 mol%, 30 to 85 mol%, or 35 to 80 mol%.

[0080] The radical polymerization initiator can also be used together with a reducing agent such as sodium sulfite, sodium hydrogen sulfite, ferrous sulfate, L-ascorbic acid, etc. to serve as a redox polymerization initiator.

[0081] (6) Chain transfer agent

[0082] The aqueous liquid may contain a chain transfer agent. Examples of the chain transfer agent include hypophosphites, mercaptans, mercaptan acids, secondary alcohols, and amines.

[0083] (7) Foaming agent

[0084] The aqueous liquid may contain a foaming agent. Examples of the foaming agent include inorganic foaming agents such as ammonium carbonate, sodium bicarbonate, and ammonium bicarbonate, nitroso compounds such as dinitrosopentamethylenetetramine, azo compounds such as azodicarbonamide and azobisisobutyronitrile, and organic foaming agents such as sulfonylhydrazine compounds such as 4,4'-oxybisbenzenesulfonylhydrazine and p-toluenesulfonylhydrazine. By using a foaming agent, the specific surface area of ​​the obtained water-absorbing resin particles can be increased. As a result, the water absorption rate of the water-absorbing resin particles can be increased.

[0085] (8) Metal chelating agents

[0086] The aqueous liquid may contain a metal chelating agent. Examples of the metal chelating agent include aminocarboxylic acid chelating agents such as diethylenetriaminepentaacetic acid and ethylenediamine-N,N'-disuccinic acid, and phosphonic acid chelating agents such as ethylenediaminetetramethylenephosphonic acid and diethylenetriaminepenta(methylphosphonic acid). By using a metal chelating agent, the metal ions in the aqueous liquid can be deactivated. As a result, a water-absorbent resin having excellent water absorption performance can be easily obtained by improving the stability of the polymerization. In addition, depolymerization is suppressed, and residual monomers are easily reduced.

[0087] [Oily liquid]

[0088] The oily liquid is a hydrophobic liquid mainly composed of a hydrocarbon dispersion medium. The oily liquid contains a hydrocarbon dispersion medium and may also contain any additives (for example, a hydrophobic polymer dispersant and / or a surfactant described below). In reversed phase suspension polymerization, the oily liquid is used as a dispersion medium for the aqueous liquid.

[0089] (1) Hydrocarbon dispersion medium

[0090] Examples of the hydrocarbon dispersion medium include chain aliphatic hydrocarbons such as n-hexane, n-heptane, 2-methylhexane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, and n-octane; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, cyclopentane, methylcyclopentane, trans-1,2-dimethylcyclopentane, cis-1,3-dimethylcyclopentane, and trans-1,3-dimethylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene. The hydrocarbon dispersion medium may be used alone or in combination of two or more.

[0091] From the viewpoint of appropriately removing the polymerization heat and facilitating the control of the polymerization temperature, the amount of the hydrocarbon dispersion medium contained in the oily liquid may be 30 to 1000 parts by mass, 50 to 650 parts by mass, 70 to 550 parts by mass, or 100 to 450 parts by mass relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer.

[0092] (2) Hydrophobic polymer dispersant

[0093] The oily liquid can include a hydrophobic polymer dispersant. As the hydrophobic polymer dispersant, for example, maleic anhydride modified polyethylene, maleic anhydride modified polypropylene, maleic anhydride modified ethylene-propylene copolymer, maleic anhydride modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene terpolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose can be enumerated. The hydrophobic polymer dispersant can be used alone or in combination with two or more.

[0094] From the viewpoint of excellent dispersion stability of the monomer, the polymer dispersant may contain at least one compound selected from the group consisting of maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene terpolymer, polyethylene, polypropylene, ethylene-propylene terpolymer, oxidized polyethylene, oxidized polypropylene and oxidized ethylene-propylene copolymer.

[0095] By using a hydrophobic polymer dispersant, the dispersion state of the aqueous liquid in the suspension is easily made more uniform, and the particle size of the water-absorbent resin particles (i.e., the specific surface area of ​​the water-absorbent resin particles) can be easily controlled by the stirring speed of the suspension. As a result, water-absorbent resin particles having the above-mentioned appropriate water absorption rate can be easily obtained. The amount of the hydrophobic polymer dispersant can be 0.05 to 10 parts by mass, 0.08 to 5 parts by mass, or 0.1 to 3 parts by mass relative to 100 parts by mass of the aqueous liquid (monomer aqueous solution).

[0096] (3) Surfactants

[0097] The oily liquid may contain a surfactant. The HLB of the surfactant may be 1 to 16, 2 to 12, or 3 to 10.5. If the HLB of the surfactant is within the above range, it is easy to control the dispersion state of the aqueous liquid in the suspension, and thus it is easy to control the shape and particle size of the water-absorbent resin particles. As a result, it is easy to obtain water-absorbent resin particles having the above-mentioned appropriate water absorption rate.

[0098] Examples of the surfactant include nonionic surfactants such as sorbitan fatty acid esters, (poly)glycerol fatty acid esters, sucrose fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oils, polyoxyethylene hydrogenated castor oils, alkyl allyl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropylene alkyl ethers, and polyethylene glycol fatty acid esters; and anionic surfactants such as fatty acid salts, alkylbenzene sulfonates, alkyl methyl taurates, polyoxyethylene alkylphenyl ether sulfates, polyoxyethylene alkyl ether sulfonates, polyoxyethylene alkyl ether phosphates, and polyoxyethylene alkyl allyl ether phosphates.

[0099] Among them, since it is easy to control the dispersion state of the aqueous liquid in the suspension, at least one compound selected from the group consisting of sorbitan fatty acid esters, polyglycerol fatty acid esters and sucrose fatty acid esters can be used. By using sorbitan fatty acid esters, the aqueous liquid in the suspension is easy to aggregate. As a result, it is easy to obtain granular water-absorbent resin particles with a large specific surface area, and the water absorption rate can be quickly adjusted. On the other hand, by using sucrose fatty acid esters, the aqueous liquid in the suspension is easy to be stably dispersed. As a result, it is easy to obtain spherical (small specific surface area) water-absorbent resin particles, and the water absorption rate can be adjusted to be slower.

[0100] <Details of the manufacturing method>

[0101] [Preparation process]

[0102] The preparation step is a step of separately preparing the oily liquid and the aqueous liquid and mixing them to prepare a suspension for polymerization. The suspension containing the surfactant can be prepared by adding the surfactant to the oily liquid and / or the aqueous liquid.

[0103] [Polymerization process]

[0104] The polymerization step is a step of heating the suspension prepared in the preparation step to perform a polymerization reaction. The polymerization temperature (temperature of the suspension) is, for example, 20 to 110° C. or 40 to 90° C. The polymerization time is, for example, 0.5 to 4 hours. In the polymerization step, the water-soluble ethylenically unsaturated monomer is polymerized to generate a particulate hydrogel polymer.

[0105] [Intermediate cross-linking process]

[0106] The method for producing the water-absorbent resin particles of the present invention may include an intermediate crosslinking step of crosslinking the hydrogel polymer. The intermediate crosslinking of the hydrogel polymer is performed, for example, by mixing the hydrogel polymer and an intermediate crosslinking agent and heating the mixture. As the intermediate crosslinking agent, the same substance as the internal crosslinking agent can be used.

[0107] The amount of the intermediate crosslinking agent may be 0.0001 to 0.03 mol, 0.0005 to 0.02 mol, or 0.001 to 0.01 mol relative to 100 mol of the water-soluble ethylenically unsaturated monomer for forming the hydrogel polymer.

[0108] The reaction temperature of the intermediate crosslinking reaction may be 60° C. or 70° C. or less, or may be below the boiling point of the hydrocarbon dispersion medium. The reaction time of the intermediate crosslinking reaction varies depending on the reaction temperature, the type and amount of the intermediate crosslinking agent, and therefore cannot be determined in general, but is generally 1 to 200 minutes, 5 to 100 minutes, or 10 to 60 minutes. The intermediate crosslinking can increase the crosslinking density inside the hydrogel polymer and control the water retention capacity and water absorption under load.

[0109] The polymerization process can be carried out in one stage or in multiple stages of more than two stages. In the case of reversed suspension polymerization in multiple stages of more than two stages, after the reversed suspension polymerization in the first stage, the reaction mixture obtained in the polymerization reaction in the first stage is mixed with ethylenically unsaturated monomers, and reversed suspension polymerization in the second stage and later is carried out by the same method as in the first stage. In the reversed suspension polymerization in each stage after the second stage, in addition to the ethylenically unsaturated monomers, the amount of the ethylenically unsaturated monomers added during the reversed suspension polymerization in each stage after the second stage can be used as a reference, and the above-mentioned free radical polymerization initiator and / or various additives can be added within the range of the ratio of each component relative to the above-mentioned ethylenically unsaturated monomers and reversed suspension polymerization can be carried out. By carrying out the polymerization process in multiple stages of more than two stages, the water-containing gel-like polymer is condensed to change its specific surface area, and the water absorption rate of the water-absorbent resin particles can be controlled.

[0110] [Particle size adjustment process]

[0111] The method for producing water-absorbent resin particles according to the present invention may include a particle size adjustment step. The particle size adjustment step can be performed by, for example, adding a coagulant such as a powdered inorganic coagulant to the system. By adding a coagulant, the particle size of the obtained water-absorbent resin particles can be increased, that is, the specific surface area can be reduced. As a result, the water absorption rate of the obtained water-absorbent resin particles can be controlled to be slow.

[0112] Examples of powdered inorganic coagulants include amorphous silica, zeolite, bentonite, alumina, talc, titanium dioxide, kaolin, clay, and hydrotalcite. From the viewpoint of high coagulation effect, the powdered inorganic coagulant may include at least one selected from the group consisting of amorphous silica, alumina, talc, and kaolin.

[0113] When the coagulant is added to the system, the addition time is, for example, between the polymerization step and the drying step described later and / or between the intermediate crosslinking step and the surface crosslinking step described later. The amount of the coagulant can be 0.001 to 1 part by mass, 0.005 to 0.5 part by mass, or 0.01 to 0.2 part by mass relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer.

[0114] The particle size of the water-absorbent resin particles can also be adjusted by controlling the dispersion state of the suspension in the polymerization step. That is, the particle size adjustment step can also be performed in the polymerization step. The dispersion state of the suspension is controlled, for example, by adjusting the rotation speed of the stirrer. For example, in the polymerization step, the particle size of the water-absorbent resin particles can be reduced by increasing the rotation speed of the stirrer, that is, the specific surface area can be controlled to be larger, and the water absorption rate of the obtained water-absorbent resin particles can be accelerated. The particle size of the water-absorbent resin particles can be controlled to be larger by slowing down the rotation speed of the stirrer, and the water absorption rate of the obtained water-absorbent resin particles can be controlled to be slower.

[0115] [Surface cross-linking process]

[0116] The method for producing water-absorbent resin particles according to the present invention may include a surface crosslinking step of crosslinking the surface of the hydrogel polymer. By crosslinking the surface of the hydrogel polymer, the water absorption under load of the obtained water-absorbent resin particles can be increased. Specifically, the crosslinking state of the surface of the hydrogel polymer can be adjusted according to the water content of the hydrogel polymer provided in the surface crosslinking step, the type and amount of the surface crosslinking agent used in the surface crosslinking step, and the water absorption under load can be controlled. Specifically, the crosslinking density of the surface of the hydrogel polymer is increased by the surface crosslinking step, so that the water absorption under load can be increased.

[0117] When the surface cross-linking process is performed, a pre-drying process for pre-adjusting the water content of the hydrogel polymer to be used in the surface cross-linking process may be included. As a drying method in the pre-drying process, for example, (a) a method of dispersing the hydrogel polymer in the oily liquid and heating it from the outside to reflux the hydrocarbon dispersion medium contained in the oily liquid and remove the water by azeotropic distillation, (b) a method of taking out the hydrogel polymer by decantation and drying it under reduced pressure, (c) a method of filtering the hydrogel polymer through a filter and drying it under reduced pressure, etc. From the perspective of simplicity in the manufacturing process, the method (a) can be adopted.

[0118] The water content of the hydrogel polymer to be subjected to the surface crosslinking step may be 5 to 130 mass %, 10 to 110 mass %, 10 to 90 mass %, 10 to 80 mass % or 15 to 60 mass %. The water content of the hydrogel polymer can be obtained by: calculating the water content of the hydrogel polymer by adding the amount obtained by subtracting the water content extracted to the outside in the pre-drying step from the water content contained in the aqueous liquid before polymerization (the water content of the hydrogel polymer after the pre-drying step) to the water content used as needed when mixing the surface crosslinking agent; and calculating the ratio of the water content of the hydrogel polymer to the mass of the water-soluble ethylenically unsaturated monomer component constituting the hydrogel polymer.

[0119] The surface crosslinking of the hydrogel polymer can be carried out, for example, by mixing the hydrogel polymer and a surface crosslinking agent and heating the mixture. The amount of the surface crosslinking agent mixed can be, for example, 0.0001 to 1 mol, 0.0005 to 0.5 mol, 0.001 to 0.1 mol, or 0.005 to 0.05 mol relative to 100 mol of the water-soluble ethylenically unsaturated monomer used to produce the hydrogel polymer.

[0120] When the water-containing gel polymer and the surface crosslinking agent are mixed, in order to make the surface crosslinking agent uniformly dispersed, water and / or a hydrophilic organic solvent can be used as a solvent for the surface crosslinking agent. As the hydrophilic organic solvent, for example, lower alcohols such as methanol, ethanol and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as dioxane and tetrahydrofuran, amides such as N,N-dimethylformamide, and sulfoxides such as dimethyl sulfoxide can be cited. The solvent for the surface crosslinking agent can be used alone or in combination of two or more.

[0121] The reaction temperature of the surface crosslinking reaction may be, for example, 60 to 200° C. or 80 to 150° C. There is a tendency that if the reaction temperature is 60° C. or higher, the surface crosslinking reaction is promoted and the reaction does not need to be too long. There is a tendency that if the reaction temperature is 200° C. or lower, the degradation of the obtained water-absorbent resin particles and the decrease in water absorption performance can be suppressed. The reaction time of the surface crosslinking reaction varies depending on the reaction temperature, the type and amount of the surface crosslinking agent, etc., and therefore cannot be determined in general, but may be 1 to 300 minutes or 5 to 200 minutes.

[0122] [Drying process]

[0123] The drying step is a step of removing water, hydrocarbon dispersion medium, etc. by applying energy such as heat from the outside to the hydrogel polymer obtained through the above steps, thereby obtaining polymer particles. As a drying method that can be used in this step, the same method as the pre-drying step that can be performed before the above-mentioned surface cross-linking step can be used. In the case of performing the surface cross-linking step, the above-mentioned surface cross-linking step can also serve as the drying step.

[0124] [Add process]

[0125] The method for producing water-absorbent resin particles according to the present invention may include a step of adding additives to polymer particles. Examples of additives include lubricants, metal chelating agents, surface modifiers, heat-resistant stabilizers, antioxidants, and antimicrobial agents.

[0126] Examples of lubricants include amorphous silicon dioxide. Examples of metal chelating agents include ethylenediaminetetraacetic acid and its salts (such as disodium ethylenediaminetetraacetate), diethylenetriaminepentaacetic acid and its salts (such as pentasodium diethylenetriaminepentaacetate). Examples of surface modifiers include polyvalent metal compounds such as aluminum sulfate, potassium alum, ammonium alum, sodium alum, (polymerized) aluminum chloride, and hydrates thereof; and polycationic compounds such as polyethyleneimine, polyethyleneamine, and polyallylamine. Depending on the hydrophilicity of the surface modifier, the hydrophilicity of the polymer particles can be controlled to a certain extent, and as a result, the water absorption rate can be controlled.

[0127] The additive can be disposed on the surface and / or inside of the polymer particles. For example, the additive can be disposed on the surface of the polymer particles by mixing the polymer particles and the additive, and the additive can be disposed inside the polymer particles by adding the additive to the above-mentioned suspension (aqueous liquid and / or oily liquid) and using it in the polymerization process.

[0128] The amount of the additive may be, for example, 0.001 to 10 parts by mass, 0.01 to 5 parts by mass, or 0.1 to 2 parts by mass based on 100 parts by mass of the polymer particles.

[0129] When the adding step is not performed, the polymer particles obtained through the drying step are the water-absorbing resin particles according to the present invention.

[0130] [Absorbent articles]

[0131] The absorbent article of the present invention comprises the water-absorbent resin particles of the present invention. By using the water-absorbent resin particles of the present invention as a nursing absorbent article, the backflow and diffusion area of ​​the absorbent article can be suppressed, thereby achieving an excellent feeling of use. The absorbent article generally comprises an absorbent body that performs a water absorption function and a protective member that protects the absorbent body.

[0132] (1) Absorber

[0133] The absorbent body may contain a resin layer containing the water-absorbent resin particles involved in the present invention and a hydrophilic fiber layer containing any hydrophilic fiber. In the case where the absorbent body contains a hydrophilic fiber layer, the resin layer and the hydrophilic fiber layer may be independent separate layers, or the resin layer and the hydrophilic fiber layer may be integrated. In other words, the water-absorbent resin particles and the hydrophilic fibers may be mixed throughout the entire absorbent body. Examples of the structure of the absorbent body include a structure in which a resin layer containing a water-absorbent resin is maintained on the upper side and / or the lower side of a hydrophilic fiber layer, a mixed structure in which the water-absorbent resin particles and the hydrophilic fibers are uniformly mixed, and a sandwich structure in which a resin layer containing water-absorbent resin particles is maintained between multiple hydrophilic fiber layers.

[0134] Examples of hydrophilic fibers include cellulose fibers such as cotton pulp and chemical pulp, and man-made cellulose fibers such as rayon and acetate. The absorbent may further include synthetic fibers made of synthetic resins such as polyamide, polyester, and polyolefin as a reinforcing agent.

[0135] Figure 1 It is a partial cross-sectional view showing an example of an absorbent article. Figure 1 The absorbent article 50 shown includes a sheet-like absorbent body 10, a first shape-retaining member 21, a second shape-retaining member 22, a protective member 30, and an adhesive 35. The absorbent body 10 is a laminate composed of a resin layer 11 including a plurality of water-absorbent resin particles 11a and a hydrophilic fiber layer 12 including hydrophilic fibers. The absorbent body 10 is arranged between the sheet-like first shape-retaining member 21 and the sheet-like second shape-retaining member 22. The entire absorbent body 10 can be surrounded by the first shape-retaining member 21 and the second shape-retaining member 22. The first shape-retaining member 21 and the second shape-retaining member 22 can be a single sheet or two separate sheets. The first shape-retaining member 21 and the second shape-retaining member 22 can be, for example, paper towels. The adhesive 35 exists between the sheet-like protective member 30 and the second shape-retaining member 22. The adhesive 35 can be, for example, a hot-melt adhesive.

[0136] The amount of the water-absorbent resin particles of the present invention in the absorbent body may be, for example, 5 to 80 mass %, 10 to 70 mass %, 15 to 65 mass % or 30 to 65 mass % based on the mass of the absorbent body (or the total amount of the hydrophilic fibers and the water-absorbent resin particles).

[0137] (2) Protective components

[0138] The protective member may be, for example, a water-permeable sheet member (liquid-permeable sheet). Examples of the liquid-permeable sheet include nonwoven fabrics, porous synthetic resin sheets, and tissues made of synthetic resins such as polyethylene, polypropylene, polyester, and polyamide. The protective member may be used alone or in combination of two or more.

[0139] In the absorbent article of the present invention, the weight per unit area of ​​the water-absorbent resin particles may be 10 to 300 g / m 2 10~200g / m 2 10~150g / m 2 50~100g / m 2 , 50~90g / m 2 , 50~80g / m 2 , 60~100g / m 2 , 60~90g / m 2 , 60~80g / m 2 , 70~100g / m 2 , 70~90g / m 2 or 70~80g / m 2 In the case where the absorbent article includes a hydrophilic fiber layer, its unit area weight may be 20 to 70 g / m 2 20~60g / m 2 20~50g / m 2 30~70g / m 2 , 30~60g / m 2 , 30~50g / m 2 40~70g / m 2 40~60g / m 2 or 40~50g / m 2 The basis weight mentioned here means the mass per unit area of ​​the absorbent article when viewed in the thickness direction of the absorbent article.

[0140] The backflow amount of the absorbent article involved in the present invention can be 0.001-5.0g, 0.001-4.0g, 0.001-3.0g, 0.001-2.0g, 0.001-1.0g, 0.001-0.1g, 0.01-5.0g, 0.01-4.0g, 0.01-3.0g, 0.01-2.0g, 0.01-1.0g, 0.01-0.1g, 0.1-5.0g, 0.1-4.0g, 0.1-3.0g, 0.1-2.0g, 0.1-1.0g, 0.5-5.0g, 0.5-4.0g, 0.5-3.0g, 0.5-2.0g or 0.5-1.0g.

[0141] The specific method for measuring the above-mentioned backflow amount is described in the Examples described below.

[0142] The diffusion area of ​​the absorbent article of the present invention can be 10 to 220 cm 2 10~200cm 2 10~180cm 2 10~160cm 2 10~140cm 2 10~120cm 2 10~110cm 2 10~100cm 2 、10~90cm 2 , 50~220cm 2 , 50~200cm 2 , 50~180cm 2 、50~160cm 2 , 50~140cm 2 , 50~120cm 2 、50~110cm 2 , 50~100cm 2 、50~90cm 2 、80~220cm 2 , 80~200cm 2 , 80~180cm 2 、80~160cm 2 、80~140cm 2 , 80~120cm 2 、80~110cm 2 、80~100cm 2 , 80~90cm 2 、90~220cm 2 、90~200cm 2 、90~180cm 2 、90~160cm 2 、90~140cm 2 , 90~120cm 2 、90~110cm 2 、90~100cm 2 100~220cm 2 100~200cm 2 100~180cm 2 100~160cm 2 100~140cm 2 100~120cm 2 or 100~110cm 2 .

[0143] The specific method for measuring the diffusion area is described in the examples described below.

[0144] According to the insights gained through in-depth research conducted by the inventors, both the backflow volume and the diffusion area of ​​absorbent articles have thresholds at which the feel of use of absorbent articles changes significantly. If the backflow volume becomes less than 1.0g, the feel of use will be significantly improved, but even if the backflow volume is further reduced, the improvement in the feel of use is minimal. It is speculated that this is because the human body is not sensitive enough to perceive a small difference in the backflow volume near the urination part. If the diffusion area exceeds 220cm 2 If the diffusion area is set to 220cm, the urine will easily flow beyond the urination area and reach more sensitive parts such as the waist, thus significantly deteriorating the feeling of use. 2 Below, the feeling of use gradually improves, but if the diffusion area is less than 90cm 2 , it will turn slightly worse if the diffusion area is less than 70cm 2 , then the specific diffusion area exceeds 220cm 2 This is considered to be because, when the diffusion area is too narrow, the height difference between the water-absorbing part of the absorbent article and other parts becomes larger due to the swelling of the water-absorbing resin particles.

[0145] The water-absorbent resin particles and absorbent articles according to the present invention can be used not only as waterproof nursing sheets but also in the fields of diapers, sanitary napkins, tampons, pet pads, and the like.

[0146] Example

[0147] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0148] [Production Example 1]

[0149] A round-bottomed cylindrical separable flask (baffle width: 7 mm, baffle length: 10 cm) with an inner diameter of 11 cm and an inner volume of 2 L and equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirrer (a stirring blade having four inclined paddle blades (blades surface-treated with fluororesin) with a blade diameter of 5 cm in two stages) was prepared. 472.30 g of n-heptane as a hydrocarbon dispersion medium and 1.104 g of sorbitan monolaurate (Nonion LP-20R, HLB value: 8.6, manufactured by NOF CORPORATION) as a surfactant were added to the flask to obtain a mixture. The mixture was heated to 50° C. while being stirred at a stirrer speed of 700 rpm to dissolve sorbitan monolaurate in n-heptane. Then, the mixture was cooled to 45° C.

[0150] Next, 92.0 g of an acrylic acid aqueous solution having a concentration of 80.5% by mass (acrylic acid: 1.03 mol) was placed in a conical flask having an internal volume of 500 mL. Next, 147.7 g of an aqueous sodium hydroxide solution having a concentration of 20.9% by mass was added dropwise while being cooled with ice from the outside to neutralize 75 mol% of the acrylic acid, thereby obtaining an acrylic acid partially neutralized aqueous solution. Next, 0.1012 g (0.374 mmol) of potassium persulfate as a water-soluble free radical polymerization initiator was dissolved in the acrylic acid partially neutralized aqueous solution, thereby preparing a monomer aqueous solution.

[0151] After the monomer aqueous solution was added to the separable flask, the inside of the system was fully replaced with nitrogen. Then, the flask was immersed in a water bath at 70°C while stirring at a stirrer speed of 700 rpm, and the state was maintained for 60 minutes to polymerize, thereby obtaining a hydrogel polymer. Then, 0.41 g of a 2 mass % aqueous solution of ethylene glycol diglycidyl ether (ethylene glycol diglycidyl ether: 0.047 mmol) was added as an intermediate crosslinking agent to the system, and the polymerization solution containing the hydrogel polymer was mixed for 30 minutes.

[0152] Then, while stirring at a stirrer speed of 1000 rpm, a dispersion obtained by pre-dispersing 0.0138 g of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) as a powdered inorganic coagulant in 100 g of n-heptane was added to the generated polymerization solution containing the hydrogel polymer, n-heptane and a surfactant, and the reaction solution (polymerization solution) was stirred for 10 minutes. Then, the flask containing the reaction solution was immersed in an oil bath at 125° C., and 104.08 g of water was extracted to the outside of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane.

[0153] Then, 4.14 g of an aqueous solution of ethylene glycol diglycidyl ether (ethylene glycol diglycidyl ether: 0.48 mmol) with a concentration of 2% by mass as a surface crosslinking agent was added, and then the internal temperature was maintained at 83±2°C for 2 hours. Then, the separable flask was heated in an oil bath at 125°C to evaporate water and n-heptane until almost no evaporation was distilled out from the system, thereby obtaining a dried product of polymer particles. The dried product was passed through a sieve with a mesh size of 850 μm, thereby obtaining 82.60 g of water-absorbent resin particles A. The physical property values ​​of the water-absorbent resin particles of Production Example 1 are shown in Table 1.

[0154] [Production Example 2]

[0155] <First stage polymerization reaction>

[0156] A round-bottom cylindrical detachable flask with an inner diameter of 11 cm and a volume of 2 L, equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and four inclined paddle blades with a blade diameter of 5 cm in two stages as a stirring blade of a stirrer, was prepared. 293 g of n-heptane as a hydrocarbon dispersion medium was added to the flask, and 0.736 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-WAX 1105A) as a hydrophobic polymer dispersant was added to obtain a mixed solution. The mixed solution was heated to 80° C. while being stirred at a stirring speed of 300 rpm to dissolve the dispersant in n-heptane. Then, the mixture was cooled to 50° C.

[0157] 92.0 g of an acrylic acid aqueous solution having a concentration of 80.5% by mass (acrylic acid: 1.03 mol) was placed in a beaker having an internal volume of 300 mL. 75 mol% of acrylic acid was neutralized by dropping 147.7 g of an aqueous sodium hydroxide solution having a concentration of 20.9% by mass while cooling with ice from the outside, thereby obtaining an acrylic acid partially neutralized aqueous solution. 0.092 g of hydroxyethyl cellulose (SUMITOMO SEIKA CHEMICALS CO., LTD., HECAW-15F) as a thickener, 0.0736 g (0.272 mmol) of potassium persulfate as a water-soluble free radical polymerization initiator, and 0.010 g (0.057 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were dissolved in the acrylic acid partially neutralized aqueous solution, thereby preparing a first-stage monomer aqueous solution.

[0158] The first-stage monomer aqueous solution was added to the separable flask and stirred at a stirrer speed of 300 rpm for 10 minutes. Then, a surfactant solution obtained by dissolving 0.736 g of HLB3 sucrose stearate (MITSUBISHI-CHEMICALFOODS CORPORATION, RYOTO SUGAR ESTER S-370) in 6.62 g of n-heptane was further added. After the inside of the system was fully replaced with nitrogen while stirring at a stirrer speed of 550 rpm, the flask was immersed in a 70°C water bath and maintained in this state for 60 minutes to perform polymerization, thereby obtaining a first-stage polymerization slurry.

[0159] <Second stage polymerization reaction>

[0160] In a beaker with an internal volume of 500 mL, 128.8 g of an acrylic acid aqueous solution having a concentration of 80.5% by mass (acrylic acid: 1.44 mol) as a water-soluble ethylenically unsaturated monomer was placed. Next, 159.0 g of a sodium hydroxide aqueous solution having a concentration of 27% by mass was added dropwise while being ice-cooled from the outside to neutralize 75 mol% of the acrylic acid, thereby obtaining an acrylic acid partially neutralized aqueous solution. Next, 0.090 g (0.333 mmol) of potassium persulfate as a water-soluble free radical polymerization initiator and 0.0116 g (0.067 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were dissolved in the acrylic acid partially neutralized aqueous solution, thereby preparing a second-stage monomer aqueous solution.

[0161] After the interior of the separable flask system was cooled to 25° C. while stirring with a stirrer at a rotation speed of 1000 rpm, the entire amount of the second-stage monomer aqueous solution was added to the first-stage polymerization slurry. After the interior of the system was replaced with nitrogen for 30 minutes, the flask was immersed in a 70° C. water bath again, and the state was maintained for 60 minutes to carry out polymerization, thereby obtaining a hydrogel polymer.

[0162] After the polymerization, 0.589 g of a 45% by mass aqueous solution of pentasodium diethylenetriamine pentaacetate was added to the obtained hydrogel polymer under stirring. Then, the flask was immersed in an oil bath set at 125° C., and 256.8 g of water was extracted to the outside of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane.

[0163] Then, 4.42 g of an aqueous solution of ethylene glycol diglycidyl ether (ethylene glycol diglycidyl ether: 0.507 mmol) with a concentration of 2% by mass as a surface crosslinking agent was added to the flask, and the internal temperature was maintained at 83±2°C for 2 hours. Then, the removable flask was heated in an oil bath at 125°C to evaporate water and n-heptane until almost no evaporation was distilled out from the inside of the system, thereby obtaining a dry product. The dry product was passed through a sieve with a mesh of 850 μm to obtain polymer particles. Amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) with a concentration of 0.5% by mass relative to the mass of the polymer particles was mixed with the polymer particles to obtain 230.2 g of water-absorbent resin particles B containing amorphous silica. The physical property values ​​of the water-absorbent resin particles of Production Example 2 are shown in Table 1.

[0164] [Production Example 3]

[0165] 0.092 g (0.339 mmol) of 2,2'-azobis(2-amidinopropane) dihydrochloride and 0.018 g (0.067 mmol) of potassium persulfate were used as water-soluble radical polymerization initiators in the first stage polymerization reaction, 0.0046 g (0.026 mmol) of ethylene glycol diglycidyl ether was used as an internal crosslinking agent in the first stage polymerization reaction, and 0.1 29 g (0.475 mmol) of water-soluble radical polymerization initiator and 0.026 g (0.096 mmol) of potassium persulfate were used as the water-soluble radical polymerization initiator used in the second stage polymerization reaction, the amount of water extracted to the outside of the system in azeotropic distillation was set to 216.7 g, and the amount of amorphous silica added to the polymer particles was set to 0.2 mass %, and 229.0 g of water-absorbent resin particles B containing amorphous silica were obtained in the same manner as in Production Example 2. The physical property values ​​of the water-absorbent resin particles of Production Example 3 are shown in Table 1.

[0166] [Production Example 4]

[0167] 233.2 g of water-absorbent resin particles B containing amorphous silica were obtained in the same manner as in Production Example 2, except that the interior of the separable flask system was cooled to 44° C. before adding the entire amount of the second-stage monomer aqueous solution to the first-stage polymerization slurry, the amount of water extracted to the outside of the system by azeotropic distillation was set to 275.8 g, and the amount of amorphous silica added to the polymer particles was set to 0.2% by mass. The physical property values ​​of the water-absorbent resin particles of Production Example 4 are shown in Table 1.

[0168] [Production Example 5]

[0169] 82.96 g of water-absorbent resin particles A were obtained in the same manner as in Production Example 1, except that the mixture of the hydrocarbon dispersion medium and the surfactant was stirred at a stirrer rotation speed of 1000 rpm, the monomer aqueous solution was stirred at a stirrer rotation speed of 1000 rpm, and the amount of water extracted to the outside of the system in azeotropic distillation was set to 103.26 g. The physical property values ​​of the water-absorbent resin particles of Production Example 5 are shown in Table 1.

[0170] [Production Example 6]

[0171] 451.4 g of n-heptane was used as a hydrocarbon dispersion medium, 1.288 g of sorbitan monolaurate was used as a surfactant, the mixture was stirred at 300 rpm, the dissolved mixture was cooled to 40° C., 0.092 g of amorphous silica was used as a powdery inorganic coagulant, the amount of water extracted to the outside of the system by azeotropic distillation was set to 104.02 g, and 8.28 g of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was used as a surface crosslinking agent, 85.60 g of water-absorbent resin particles A were obtained in the same manner as in Production Example 1. The physical property values ​​of the water-absorbent resin particles of Production Example 6 are shown in Table 1.

[0172] [Table 1]

[0173]

[0174] The water-absorbent resin particles obtained in each Production Example were used to produce water-absorbent resin particles and absorbent articles according to Examples and Comparative Examples, and their physical properties were evaluated.

[0175] [Example 1]

[0176] <Production of water-absorbent resin particles>

[0177] 0.2 g of the water-absorbent resin particles prepared in Production Example 1 and 2.8 g of the water-absorbent resin particles prepared in Production Example 2 were uniformly mixed to obtain water-absorbent resin particles of Example 1. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 1.

[0178] <Manufacturing of absorbent articles>

[0179] A 20 cm × 60 cm square with a weight of 16 g / m 2 The first shape-retaining member (toilet paper) was obtained. 5.4 g of hydrophilic fibers (pulverized pulp) uniformly mixed by air papermaking using an airflow type mixing device (manufactured by Autech, pad former) were stacked on the first shape-retaining member, thereby forming a hydrophilic fiber layer on the entire upper surface of the first shape-retaining member, thereby obtaining a laminate. After cutting off the inner area of ​​10 cm from both ends in the longitudinal direction of the laminate, the laminate was divided into two equal parts, thereby obtaining two laminates of 20 cm×20 cm in size.

[0180] The water-absorbent resin particles (3.0 g) of Example 1 were uniformly dispersed on the hydrophilic fiber layer of the laminate to form a resin layer. A 20 cm×20 cm-sized sheet with a unit area weight of 16 g / m 2The second shape-retaining member (toilet paper) is added to produce an absorbent body in which the first shape-retaining member, the hydrophilic fiber layer, the resin layer and the second shape-retaining member are stacked in this order from bottom to top.

[0181] After applying a load of 424 kPa to the absorbent body for 30 seconds, a hot air nonwoven fabric (manufactured by Rengo Co., Ltd., 21 g / m 2 ) as a protective component is laminated on the second shape-maintaining component to obtain an absorbent article. On the hot air nonwoven fabric, 0.1 g of hot melt adhesive (Henkel Ja pan Ltd., ME-765E) was pre-coated using a hot melt coater (HALLYS Corporation, pump: Marshal 150, workbench: XA-DT, tank setting temperature: 150°C, hose setting temperature: 165°C, gun tip setting temperature: 170°C) in a spiral stripe pattern of 20 rows with 10 mm intervals. The absorbent resin particles of the obtained absorbent article have a unit area weight of 75 g / m 2 The hydrophilic fiber (pulverized pulp) has a unit area weight of 45 g / m 2 The backflow amount and diffusion area of ​​the absorbent article of Example 1 were measured by the measurement method described below. The measurement results are shown in Table 2.

[0182] [Example 2]

[0183] <Production of water-absorbent resin particles>

[0184] 3.0 g of the water-absorbent resin particles prepared in Production Example 4 were used as the water-absorbent resin particles in Example 2 as they were.

[0185] <Manufacturing of absorbent articles>

[0186] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 2 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 2 were measured. Table 2 shows the measurement results.

[0187] [Example 3]

[0188] <Production of water-absorbent resin particles>

[0189] 0.4 g of the water-absorbent resin particles prepared in Production Example 1 and 2.6 g of the water-absorbent resin particles prepared in Production Example 2 were uniformly mixed to obtain water-absorbent resin particles of Example 3. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 3.

[0190] <Manufacturing of absorbent articles>

[0191] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 3 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 3 were measured. Table 2 shows the measurement results.

[0192] [Example 4]

[0193] <Production of water-absorbent resin particles>

[0194] 0.75 g of the water-absorbent resin particles prepared in Production Example 1 and 2.25 g of the water-absorbent resin particles prepared in Production Example 2 were uniformly mixed to obtain water-absorbent resin particles of Example 4. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 4.

[0195] <Manufacturing of absorbent articles>

[0196] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 4 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 4 were measured. Table 2 shows the measurement results.

[0197] [Example 5]

[0198] <Production of water-absorbent resin particles>

[0199] 1.5 g of the water-absorbent resin particles prepared in Production Example 1 and 1.5 g of the water-absorbent resin particles prepared in Production Example 4 were uniformly mixed to obtain water-absorbent resin particles of Example 5. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 5.

[0200] <Manufacturing of absorbent articles>

[0201] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 5 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 5 were measured. Table 2 shows the measurement results.

[0202] [Example 6]

[0203] <Production of water-absorbent resin particles>

[0204] 1.5 g of the water-absorbent resin particles prepared in Production Example 1 and 1.5 g of the water-absorbent resin particles prepared in Production Example 2 were uniformly mixed to obtain water-absorbent resin particles of Example 6. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 6.

[0205] <Manufacturing of absorbent articles>

[0206] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 6 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 6 were measured. Table 2 shows the measurement results.

[0207] [Example 7]

[0208] <Production of water-absorbent resin particles>

[0209] 1.6 g of the water-absorbent resin particles prepared in Production Example 1 and 1.4 g of the water-absorbent resin particles prepared in Production Example 3 were uniformly mixed to obtain water-absorbent resin particles of Example 7. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 7.

[0210] <Manufacturing of absorbent articles>

[0211] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 7 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 7 were measured. Table 2 shows the measurement results.

[0212] [Example 8]

[0213] <Production of water-absorbent resin particles>

[0214] 1.8 g of the water-absorbent resin particles prepared in Production Example 1 and 1.2 g of the water-absorbent resin particles prepared in Production Example 2 were uniformly mixed to obtain water-absorbent resin particles of Example 8. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 8.

[0215] <Manufacturing of absorbent articles>

[0216] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 8 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 8 were measured. Table 2 shows the measurement results.

[0217] [Example 9]

[0218] <Production of water-absorbent resin particles>

[0219] 2.6 g of the water-absorbent resin particles prepared in Production Example 1 and 0.4 g of the water-absorbent resin particles prepared in Production Example 3 were uniformly mixed to obtain water-absorbent resin particles of Example 9. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 9.

[0220] <Manufacturing of absorbent articles>

[0221] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 9 were used. The backflow amount and diffusion area of ​​the absorbent article of Example were measured. The measurement results are shown in Table 2.

[0222] [Example 10]

[0223] <Production of water-absorbent resin particles>

[0224] 3.0 g of the water-absorbent resin particles prepared in Production Example 1 were used as the water-absorbent resin particles in Example 10 as they were.

[0225] <Manufacturing of absorbent articles>

[0226] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 10 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 10 were measured. Table 2 shows the measurement results.

[0227] [Example 11]

[0228] <Production of water-absorbent resin particles>

[0229] 1.5 g of the water-absorbent resin particles prepared in Production Example 2 and 1.5 g of the water-absorbent resin particles prepared in Production Example 6 were uniformly mixed to obtain water-absorbent resin particles of Example 11. Table 2 shows the physical property values ​​of the water-absorbent resin particles of Example 11.

[0230] <Manufacturing of absorbent articles>

[0231] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Example 11 were used. The backflow amount and diffusion area of ​​the absorbent article of Example 11 were measured. Table 2 shows the measurement results.

[0232] [Comparative Example 1]

[0233] <Production of water-absorbent resin particles>

[0234] 3.0 g of the water-absorbent resin particles prepared in Production Example 2 were used as the water-absorbent resin particles in Comparative Example 1 as they were.

[0235] <Manufacturing of absorbent articles>

[0236] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Comparative Example 1 were used. The backflow amount and diffusion area of ​​the absorbent article of Comparative Example 1 were measured. The measurement results are shown in Table 2.

[0237] [Comparative Example 2]

[0238] <Production of water-absorbent resin particles>

[0239] 3.0 g of the water-absorbent resin particles prepared in Production Example 3 were used as the water-absorbent resin particles in Comparative Example 2 as they were.

[0240] <Manufacturing of absorbent articles>

[0241] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Comparative Example 2 were used. The backflow amount and diffusion area of ​​the absorbent article of Comparative Example 2 were measured. The measurement results are shown in Table 2.

[0242] [Comparative Example 3]

[0243] <Production of water-absorbent resin particles>

[0244] 3.0 g of the water-absorbent resin particles prepared in Production Example 5 were used as the water-absorbent resin particles in Comparative Example 3 as they were.

[0245] <Manufacturing of absorbent articles>

[0246] An absorbent article was produced in the same manner as in Example 1 except that the water-absorbent resin particles of Comparative Example 3 were used. The backflow amount and diffusion area of ​​the absorbent article of Comparative Example 3 were measured. Table 2 shows the measurement results.

[0247] [Table 2]

[0248]

[0249] In addition, for Example 1, Example 3 to Example 9 containing water-absorbent resin particles A and water-absorbent resin particles B, the weighted average values ​​of various physical properties were calculated as predicted values ​​based on the mass ratio of the water-absorbent resin particles A and the water-absorbent resin particles B contained in these Examples, and various physical properties (physical properties of water-absorbent resin particles and evaluation of water-absorbent articles) of Example 2, Example 10, Comparative Example 1 and Comparative Example 2 containing a single type of water-absorbent resin particles A or water-absorbent resin particles B. These predicted values ​​are also shown in Table 2.

[0250] As shown in Table 2, in the evaluation of absorbent articles, the diffusion area ratio was superior to the weighted average value (predicted value) in Example 1, Example 3 to Example 9 including the water-absorbent resin particles A and the water-absorbent resin particles B, and in particular, the diffusion area and the backflow amount ratio were superior to the weighted average value (predicted value) in Example 1, Example 3 to Example 6 and Example 8. Thus, it was confirmed that the examples using the water-absorbent resin particles A and the water-absorbent resin particles B simultaneously exerted a synergistic effect on the performance of the absorbent article.

[0251] [Method for measuring physical properties of water-absorbent resin particles]

[0252] (Water absorption speed)

[0253] The water absorption rate test based on the Vortex method was carried out at room temperature. 50±0.1g of physiological saline was weighed in a beaker with a volume of 100mL. A magnetic stirrer (8mmφ×30mm without ring) was put in, and the beaker was immersed in a constant temperature water tank, and the liquid temperature was adjusted to 25±0.2°C. Next, the beaker was placed on the magnetic stirrer, and after the physiological saline was vortexed at a speed of 600rpm, 2.0g of water-absorbent resin particles were quickly added to the beaker. A stopwatch was used to measure the time (seconds) from the moment the water-absorbent resin particles were added to the moment the vortex on the liquid surface subsided, and it was used as the water absorption rate of the water-absorbent resin particles.

[0254] (water retention capacity)

[0255] The water retention capacity test was conducted at room temperature. A cotton bag (broad-width cotton cloth No. 60, 100 mm wide x 200 mm long) containing 2.0 g of water-absorbent resin particles was placed in a beaker of 500 mL. 500 g of physiological saline was injected into the cotton bag containing the water-absorbent resin particles at one time in a manner that did not cause lumps, the upper part of the cotton bag was tied with a rubber band, and the bag was left to stand for 30 minutes to allow the water-absorbent resin particles to swell. The cotton bag was dehydrated for 1 minute after 30 minutes using a dehydrator (manufactured by KOKUSAN Co. Ltd., product number: H-122) with a centrifugal force set to 167 G. The mass Wa (g) of the cotton bag containing the swollen gel after dehydration was measured. The same operation was performed without adding water-absorbent resin particles, and the empty mass Wb (g) of the cotton bag when wet was measured. The water retention capacity of physiological saline was calculated according to the following formula.

[0256] Water retention capacity of saline solution [g / g] = (Wa-Wb) / 2.0

[0257] (Water absorption under load)

[0258] use Figure 2The measuring device Y shown measures the amount of water absorbed by physiological saline under load (under pressure) of water-absorbent resin particles at room temperature. The measuring device Y is composed of a burette portion 61, a catheter 62, a measuring table 63, and a measuring portion 64 placed on the measuring table 63. The burette portion 61 has: a burette 61a extending in the vertical direction; a rubber plug 61b arranged at the upper end of the burette 61a; a stopcock 61c arranged at the lower end of the burette 61a; an air introduction tube 61d extending into the burette 61a near the stopcock 61c; and a stopcock 61e arranged on the other end side of the air introduction tube 61d. The catheter 62 is installed between the burette portion 61 and the measuring table 63. The inner diameter of the catheter 62 is 6 mm. A hole with a diameter of 2 mm is opened in the central part of the measuring table 63, and the catheter 62 is connected. The measuring part 64 comprises: a cylinder 64a (made of acrylic resin (plexiglass)); a nylon mesh 64b bonded to the bottom of the cylinder 64a; and a weight 64c. The inner diameter of the cylinder 64a is 20 mm. The mesh of the nylon mesh 64b is 75 μm (200 mesh). During the measurement, the water-absorbent resin particles 65 to be measured are evenly spread on the nylon mesh 64b. The diameter of the weight 64c is 19 mm, and the mass of the weight 64c is 59.8 g. The weight 64c is placed on the water-absorbent resin particles 65, and can apply a load of 2.07 kPa to the water-absorbent resin particles 65.

[0259] After 0.100 g of water-absorbent resin particles 65 were placed in the cylinder 64a of the measuring device Y, a weight 64c was placed and the measurement was started. Air of the same volume as the physiological saline absorbed by the water-absorbent resin particles 65 was quickly and smoothly supplied to the inside of the burette 61a through the air introduction tube, so the reduction in the water level of the physiological saline inside the burette 61a became the amount of physiological saline absorbed by the water-absorbent resin particles 65. The scale of the burette 61a was engraved from 0 mL to the bottom at intervals of 0.5 mL. As the water level of the physiological saline, the scale Va of the burette 61a before the start of water absorption and the scale Vb of the burette 61a 60 minutes after the start of water absorption were read, and the water absorption under load was calculated by the following formula.

[0260] Water absorption under load [mL / g] = (Vb-Va) / 0.1

[0261] (Median particle size)

[0262] The water-absorbent resin particles were passed through a sieve with a mesh size of 250 μm of a JIS Z 8801-1 standard sieve. When the amount remaining on the sieve was 50% by mass or more relative to the total amount, the median particle size was measured using the following combination of sieves (A), and when it was less than 50% by mass, the median particle size was measured using the following combination of sieves (B).

[0263] (A) A sieve with a mesh size of 710 μm, a sieve with a mesh size of 600 μm, a sieve with a mesh size of 500 μm, a sieve with a mesh size of 425 μm, a sieve with a mesh size of 300 μm, a sieve with a mesh size of 250 μm, a sieve with a mesh size of 150 μm, and a tray are combined in this order from top to bottom.

[0264] (B) A sieve with a mesh size of 425 μm, a sieve with a mesh size of 250 μm, a sieve with a mesh size of 180 μm, a sieve with a mesh size of 150 μm, a sieve with a mesh size of 106 μm, a sieve with a mesh size of 75 μm, a sieve with a mesh size of 45 μm, and a tray are combined in this order from top to bottom.

[0265] Water-absorbent resin particles were placed in the uppermost sieve and vibrated for 20 minutes using a continuous fully automatic sonic vibration sieve measuring device (Robot Shifter RPS-205, manufactured by SEISHIN ENTERPRISE Co., Ltd.) to perform classification. After classification, the mass of the water-absorbent resin particles remaining on each sieve was calculated as a mass percentage relative to the total mass, and the water-absorbent resin particles were accumulated in descending order of particle size, and the relationship between the mesh size of the sieve and the cumulative value of the mass percentage of the water-absorbent resin particles remaining on the sieve was plotted on a logarithmic probability paper. The plotted points on the probability paper were connected by a straight line, and the particle size corresponding to 50% of the cumulative mass percentage was taken as the median particle size.

[0266] <Evaluation Method for Absorbent Articles>

[0267] (Test solution)

[0268] A test solution was prepared by blending and dissolving an inorganic salt in ion exchange water in the following manner and further blending a small amount of Blue No. 1. The absorbent article was evaluated using the test solution.

[0269] Test fluid composition

[0270] Deionized water: 4955.5g

[0271] ·NaCl: 39.0g

[0272] ·CaCl2

[0273] 2H2O: 1.5g

[0274] MgCl2

[0275] 7H2O: 4.0g

[0276] Edible blue No. 1 (for coloring)

[0277] (counterflow)

[0278] At room temperature, an absorbent article was placed on a horizontal table. Next, a pump (INTEGRA Biosciences, DOSE IT P910) connected to an inlet with an inner diameter of 0.4 mm was used to drip 30 mL of a test solution adjusted to 25 ± 1 ° C from 1 cm above the absorbent article to the center of the absorbent article over 8 seconds. One minute after the completion of the dripping of the test solution, a filter paper (ADVANTEC No.51A, formed into 100 mm × 100 mm) of about 75 g of mass was placed near the center of the absorbent article, and a weight of about 0.7 psi (bottom surface is 100 mm × 100 mm, 5.0 kg) was quickly placed on it, and a load was applied for 5 seconds. Then, the weight and filter paper were removed, and the mass of the test solution absorbed by the filter paper was measured. The increase in the filter paper before and after the test was set as the backflow [g].

[0279] (Diffusion Area)

[0280] The absorbent article was placed on a horizontal table at room temperature. Next, using a pump (DOSE IT P910 manufactured by INTEGRA Biosciences) connected to an inlet with an inner diameter of 0.4 mm, 30 mL of a test solution adjusted to 25±1°C was dripped from 1 cm above the absorbent article to the center of the absorbent article over 8 seconds. Two minutes after the completion of the dripping of the test solution, the longitudinal length (longitudinal diffusion length) and the lateral length (lateral diffusion length) of the diffusion area of ​​the test solution through the center of the absorbent article were measured. Based on the respective diffusion lengths, the diffusion area [cm 2 ].

[0281] Diffusion area [cm 2 ] = (longitudinal diffusion length / 2) × (transverse diffusion length / 2) × 3.14

[0282] Industrial Applicability

[0283] According to the water-absorbent resin particles of the present invention, the backflow and diffusion area of ​​the absorbent article can be suppressed, so the replacement frequency of the absorbent article (for example, pet pads) can be reduced. As a result, the use amount of the water-absorbent resin particles and materials other than the water-absorbent resin particles contained in the absorbent article (for example, raw materials derived from natural substances (biomass resources) such as pulp and non-woven fabrics) can be suppressed, which can contribute to the protection of the global environment.

[0284] Description of Reference Numerals

[0285] 10-absorbent body, 11-resin layer, 11a-water-absorbent resin particles, 12-hydrophilic fiber layer, 21-first shape-maintaining member, 22-second shape-maintaining member, 30-protective member, 35-adhesive, 50-absorbent article, 61-burette portion, 61a-burette, 61b-rubber plug, 61c-stopcock, 61d-air introduction tube, 61e-stopcock, 62-conduit, 63-measuring table, 64-measuring portion, 64a-cylinder, 64b-nylon net, 64c-weight, Y-measuring device.

Claims

1. A water-absorbent resin particle having a water absorption rate of 3 to 30 seconds and a water absorption amount of 10 mL / g or more under a load of 2.07 kPa.

2. The water-absorbent resin particle according to claim 1, wherein The water absorption speed is 6 to 10 seconds, and the median particle size is greater than 150 μm.

3. The water-absorbent resin particle according to claim 1 or 2, wherein The water-absorbent resin particles include water-absorbent resin particles A and water-absorbent resin particles B. The water absorption rate of the water-absorbent resin particles A is 5 seconds or less, and the water absorption amount of the water-absorbent resin particles A under a load of 2.07 kPa is 8 to 35 mL / g. The water absorption rate of the water-absorbent resin particles B is 15 seconds or more, and the water absorption amount of the water-absorbent resin particles B under a load of 2.07 kPa is 20 to 35 mL / g.

4. An absorbent article comprising the water-absorbent resin particles according to claim 1 or 2.

Citation Information

Patent Citations

  • Water absorbing composite sheet for care sheet, manufacturing method thereof, and care sheet

    JP2005323842A